Prevalence of Asthma in Pregnant Women at Rumah Sakit Universitas Airlangga in 2022–2023 - Ardyan, Raghda Amanda; Arief Bakhtiar; Sofia Al Farizi (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
Introduction: Asthma is a heterogeneous disease, typically characterized by chronic airway inflammation. The condition is defined by a history of respiratory symptoms, including wheezing, shortness of breath, chest tightness, and coughing, which vary over time and intensity, in addition to variable expiratory airflow limitation. As the prevalence of asthma in the community continues to increase, cases of asthma in pregnancy are also becoming more common. This study aims to determine the prevalence of asthma among pregnant women at Rumah Sakit Universitas Airlangga during 2022-2023. Objectives: The objective of this study is to determine the prevalence of asthma among pregnant women at Rumah Sakit Universitas Airlangga during the period of 2022-2023. Methods: This study employed a descriptive quantitative method with a cross-sectional research design. Data measurement and observation were conducted at a single time point using secondary data from January 2022 to December 2023 in a retrospective manner. Results: Among 8.170 pregnant women at Rumah Sakit Universitas Airlangga, 25 were diagnosed with asthma, resulting in a prevalence of 0,31%. Conclusions: The data indicates that the prevalence of pregnant women with asthma diagnoses at Rumah Sakit Universitas Airlangga was lower than the 0.31% reported in previous literature.